Assessing community consequences of implementing hot spots policing in residential areas: findings from a randomized field trial - Kochel, Tammy Rinehart (Journal of experimental criminology, 2017)
This paper reports on the results of an experiment examining the community impact of collaborative problem solving versus directed patrol hot spots policing approaches relative to standard policing practices. The focus is the impact on community perceptions of police.